Consumer safety complaints and organizational learning: evidence from the automotive industry. Issue 10 (29th November 2018) - Sarkar, Sourish; Rajagopalan, Balaji
Abstract : Purpose: The purpose of this paper is to investigate the value of information in consumer safety complaints for organizational learning. Design/methodology/approach: Empirical analysis of this study uses a novel secondary data set, which is formed by combining complaints data filed with the National Highway Traffic Safety Administration (NHTSA) for potential safety defects, and design change information from 2003 to 2011 model-year vehicles in the USA. Findings: First, the paper demonstrates the value of information embedded in complaints. Second, in the case of radical product redesigns, owing to the lack of direct applicability of consumer feedback based learning, the impact of learning on product safety is found to be muted, third, the results suggest that the safety complaint rates vary by vehicle classes/categories and, fourth, the findings differ from prior research conclusions on vehicle quality. Prior research finds the debuting car models have the lowest repair rates among all car models produced in a given year, but the current study finds the debuting models to have the highest rates of safety complaints. Originality/value: Quality management literature rarely examines the safety complaints data (which, unlike other consumer feedbacks, focuses exclusively on the safety hazards due to flaws that result in accidents). This paper fills the gap in literature by linking safety complaints with future product quality and organizational learning.